Microstructures and Mobility in the Byzantine World - Rapp, Claudia; Stouraitis, Yannis (2024)
Preview The volume – whose chapters originated at panels at the International Byzantine Congress in Belgrade and at the IMC in Leeds – seeks to offer an introduction into various aspects of social and geographical mobility, and the intrinsic relationship between the two, as well as into the microstructures of social action in the Byzantine world during the high and late Middle Ages. Based on a balanced approach to the role of personal agency and social structure, the authors of the individual chapters seek to clarify how and why various kinds of people mobilized to either change place and/or social position, or to form groups whose actions shaped social reality.